Selective sequestering of multi-walled carbon nanotubes in self-assembled block copolymer - Park, Incheol; Lee, Wonmok; Kim, Junkyung; Park, Min; Lee, Hyunjung (ELSEVIER SCIENCE SA, 2007)
Block copolymer (BCP) can self-assemble into various nanostructures thorough their unique microphase separation. The role of soft materials such as block copolymers in sequestering the functional materials (as nanoparticles and biomaterials) aims at templating the nanostructure to achieve its desirable function. Depending on functional elements incorporated in BCP, various applications have been proposed such as the mechanically reinforced materials or biosensors or wave-guiding photonic materials. While most of nano-elements are isotropic in shape (i.e. sphere), the carbon nanotubes (CNTs) exhibit the high aspect ratio. A typical CNT has the diameter of several nm and the length of a few mu m. CNTs generally have a superior electrical conductivity and mechanical strength, thus its composite with soft materials can form a platform material for flexible display panel or e-paper. In this study, we demonstrated in situ functionalization of multi-walled carbon nanotube (MWNT) with polymer via emulsion polymerization. Polystyrene-functionalized MWNT was prepared in an aqueous solution containing styrene monomer, non-ionic surfactant and the cationic coupling agent ([2-(methacryloyloxy)ethyl I trimethyl ammonium chloride, MATMAC) and produced PS-functionalized MWNTs by dissolving them in toluene over 72 It. Consequently, it increased the solubility and the dispersion of nanotubes even with a low degree of functionalization. A lamellar forming polystyrene-b-isoprene (400k-360k, PS-b-PI) was used as the structure-guiding materials in ordering the PS-functionalized MWNTs anisotropically in PS domain. This method might contribute to the fabrication of CNT-embedded nanofunctional materials by controlling the orientation and the spatial distribution very effectively. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: TRANSFER RADICAL POLYMERIZATION; FUNCTIONAL MATERIALS; COMPOSITES; FILMS; DISPERSION; ALIGNMENT; MATRIX